1990
DOI: 10.1159/000132963
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the insulin receptor-related receptor gene to human chromosome 1

Abstract: DNA encoding the insulin receptor-related receptor (1RR), a novel receptor whose predicted primary structure is similar to those of the insulin and insulin-like growth factor I receptors, has been used in Southern blot analysis of DNA from human × mouse somatic cell hybrids to assign the IRR gene (INSRR) to human chromosome 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It is unlikely that trkA and IRR are driven by a bi-directional promoter; however, they are co-expressed at the cellular level in both neuronal and non-neuronal tissues in rat (Reinhardt et al, 1994;Tsuji et al, 1996), suggesting that they may share regulatory elements acting both in cis and in trans. Similar genomic arrangements may exist in other species; thus, both the IRR and trkA genes are located in human chromosome 1 (Shier et al, 1990;Valent et al, 1997). We have shown that a small region of 150 nucleotides, 5' to the mouse trkA gene, is required for promoter activity and for cell-type speci®c transcription.…”
mentioning
confidence: 61%
“…It is unlikely that trkA and IRR are driven by a bi-directional promoter; however, they are co-expressed at the cellular level in both neuronal and non-neuronal tissues in rat (Reinhardt et al, 1994;Tsuji et al, 1996), suggesting that they may share regulatory elements acting both in cis and in trans. Similar genomic arrangements may exist in other species; thus, both the IRR and trkA genes are located in human chromosome 1 (Shier et al, 1990;Valent et al, 1997). We have shown that a small region of 150 nucleotides, 5' to the mouse trkA gene, is required for promoter activity and for cell-type speci®c transcription.…”
mentioning
confidence: 61%
“…Previously, the INSRR locus was localized to chromosome 1 by the use of a human hamster somatic cell panel (Shier et al, 1990). As a first step to assess a possible role of INSRR in heritable forms of diabetes or neurodegenerative disease, we carried out a regional mapping of the human INSRR locus.…”
Section: Rationale and Significancementioning
confidence: 99%
“…Interestingly, the insulin receptor-related receptor gene has been localized to human chromosome 1, a hot spot for mutations, deletions and rearrangements in human neuroblastoma tumors [14]. Since the presence of endogenous IRR in neuroblastoma tumors as measured by a kinase immunoprecipitation assay seems to be related to the stage of the tumors [5], elucidation of both biological function and natural ligand of the receptor might prove to be important and of clinical relevance in the area of neuroblastoma research.…”
Section: 5%mentioning
confidence: 99%